Ecological security : the foundation of sustainable development - Singh, Samar (ed.) (Delhi Shipra Publications, 2007)
The basis and raison d'être of the concept of Ecological Security lies in the linking of two substantive words 'ecology' and 'security', connoting an ecological condition in safe keeping, firmly fastened and guaranteed against minimum loss or damage. This volume contains papers based on in depth studies by eminent persons on different aspects of a wide ranging, complex and contemporary subject.
Keywords: IAS as an editor; 1962 batch; Sustainable development